Pengaruh pemberian inulin sebagai prebiotik terhadap efisiensi pemanfaatan pakan dan parameter hematologi ikan nila merah (Oreochromis sp.): The effect of different dosages of inulin on efficiency of feed utilization and immunity response of Red Tilapia (Oreochromis sp.) - Yusuf, Muhammad Abdul; Susanto , Adi; Agustina, Agustina (Faculty of Fisheries and Marine Science, Mulawarman University, 2023)
This research was conducted to determine the effect of inulin on the efficiency of feed utilization and the hematological parameters of red tilapia. This study used a completely randomized design (CRD), with 4 treatments and 3 replications. The doses of inulin used in the treatment were 0,00 g/kg, 1,00 g/kg, 2,00 g/kg and 4,00 g/kg. Tilapia with body length of 6,00-6,50 cm and weight of 4,00-4,50 g were reared in a plastic container with a volume of 40 l of water in a semi-closed water recirculation system for 30 days. Fish were fed with treatment using the at satiation method with a frequency of 3 times a day. The results showed that the administration of inulin had no effect on the efficiency of feed utilization (p>0,05), but gave the best value on hemoglobin levels, hematocrit levels, total erythrocytes, total leukocytes, lymphocyte levels, monocyte levels, and neutrophil levels at dose 2,00 g/kg (p<0,05).